Minos Beach Art Symposium (Crete : Minos Beach Hotel, 1988)
Benglis, Lynda ; Buren, Daniel ; Caniaris, Vlassis ; Chia, Sandro ; Ciarli, Carlo ; Daphnis, Nassos ; Gallo, Vincent ; Gianakos, Cristos ; Hadjipateras, Mark ; Jacober, Ben ; Kapoor, Anish ; Kapsalis, Michael ; Karella, Marina ; Kosutch, Joseph ; Mattiacci, Eliseo ; Mylonas, Eleni ; Oppenheim, Dennis ; Pastra, Nausica ; Poirier, Anne & Patrick ; Raynaud, Patrick ; etc.
Minos Beach Art Symposium, at Minos Beach Hotel, Crete, from 11 June to 15 October 1988.
boek